2022
DOI: 10.1609/aaai.v36i11.21460
|View full text |Cite
|
Sign up to set email alerts
|

Field Study in Deploying Restless Multi-Armed Bandits: Assisting Non-profits in Improving Maternal and Child Health

Abstract: The widespread availability of cell phones has enabled non-profits to deliver critical health information to their beneficiaries in a timely manner. This paper describes our work to assist non-profits that employ automated messaging programs to deliver timely preventive care information to beneficiaries (new and expecting mothers) during pregnancy and after delivery. Unfortunately, a key challenge in such information delivery programs is that a significant fraction of beneficiaries drop out of the program. Yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…We briefly note here that unless the MDP's state space C is relatively small, then the (data-dependent) permutation set Π 4 will typically be quite small and virtually no randomization in permutations can be performed. There are, however, settings in which the state space C is small, such as in the restless multiarmed bandit considered by Mate et al (2020Mate et al ( , 2021 in the context of patient adherence monitoring and well-being, in which our test can be used effectively.…”
Section: Conditional Independence Testingmentioning
confidence: 99%
“…We briefly note here that unless the MDP's state space C is relatively small, then the (data-dependent) permutation set Π 4 will typically be quite small and virtually no randomization in permutations can be performed. There are, however, settings in which the state space C is small, such as in the restless multiarmed bandit considered by Mate et al (2020Mate et al ( , 2021 in the context of patient adherence monitoring and well-being, in which our test can be used effectively.…”
Section: Conditional Independence Testingmentioning
confidence: 99%
“…Our previous study conducted in April 2021 Mate et al. (2022) is the first to present real‐world service quality improvement using RMABs in the context of mMitra program. This study tested an RMAB‐based policy against two baselines of interest, and showed RMAB outperforming its competitors.…”
Section: Restless Multi‐armed Bandits (Rmab)mentioning
confidence: 99%
“…Furthermore, whereas RMAB achieves statistically significant improvement against CSOC (p<0.05$p &lt; 0.05$) and RR (p<0.1$p &lt; 0.1$), RR fails to achieve any statistically significant improvement over CSOC (see Mate et al. 2022 for more details). This key result forms the basis of relying on RMAB‐based strategy over other non‐AI strategies as a basis of Saheli .…”
Section: Restless Multi‐armed Bandits (Rmab)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bandit optimization is a very general framework for sequential decision making when the dynamics of the underlying environment are unknown a priori. It has been well studied over the past few decades, and has shown great empirical success in areas including ad placement, clinical trials [3,4]. Such standard bandit methods often assume the decision maker has access to the entire user context or user state.…”
Section: Introductionmentioning
confidence: 99%